PENGARUH KOMUNIKASI PEMASARAN BASO ACI AKANG TERHADAP MINAT BELI KONSUMEN DI MASA PANDEMI COVID-19 (Survei Pada Followers Akun Instagram @basoaciakang) - Nina Anissa (2022)
The ongoing COVID-19 pandemic has had a significant impact on Micro, Small, and Medium Enterprises (MSMEs), particularly in the food and beverage sector. The decline in sales figures and the level of public consumption during the Covid-19 pandemic became a significant problem for MSME actors, one of which was Baso Aci Akang. Baso Aci Akang uses marketing communications as a marketing strategy to attract consumer interest in purchasing products during the Covid-19 pandemic. This study aims to determine how much influence Baso Aci Akang's marketing communications have on consumer buying interest during the Covid-19 pandemic. The research method used is quantitative with an explanative type. The research data collection used a survey method by distributing questionnaires to 100 respondents following the Instagram account @basoaciakang. The theory used in this research is the theory of planned behavior to measure individual behavior and interest in a product. The researcher conducted a validity test, reliability test, correlation test, coefficient of determination test, simple linear regression test, and hypothesis testing. The results showed that there was a strong relationship between Baso Aci Akang marketing communications and consumer buying interest during the Covid-19 pandemic with a correlation value of 0.698. The results of the coefficient of determination show that the influence of Baso Aci Akang marketing communications on consumer buying interest during the Covid-19 pandemic is 30% and the rest is influenced by other factors outside the study, such as marketing activities using other social media and e-commerce, product quality, product trust, and product satisfaction. The results of the study were strengthened by the results of hypothesis testing which stated that H0 was rejected and H1 was accepted, meaning that there was a significant influence on Baso Aci Akang's marketing communications on consumer buying interest during the Covid-19 pandemic.